Risk factor analysis of bovine leukemia virus infection in dairy cattle in Egypt. (October 2020) - Selim, Abdelfattah; Megahed, Ameer A.; Kandeel, Sahar; Abdelhady, Abdelhamed
Highlights: Bovine leukemia virus affects dairy cattle and cause severe economic losses. The prevalence of BLV increase with number of parities. Geographic location have no impact on the prevalence of BLV. Intensive surveillance for BLV is important to control the disease in Egypt. Abstract: Identification of the risk factors associated with Enzootic bovine leukosis (EBL) is essential for the adoption of potentially prevention strategies. Accordingly, our objectives were to determine the geographic distribution of Bovine Leukemia Virus (BLV) infection and identify the risk factors associated with cow-level BLV infection in the Egyptian dairy cattle. A cross-sectional study was conducted on 1299 mixed breed cows distributed over four provinces in the Nile Delta of Egypt in 2018. The randomly selected cows on each farm were serologically tested for BLV, and the cow's information was obtained from the farm records. Four variables (geographic location, herd size, number of parities, and age) were used for risk analysis. A total of 230 serum samples (17.7 %) were serologically positive for BLV. The highest prevalence of BLV infection was associated with parity (OR = 3.4, 95 %CI 2.4–4.9) with 80 % probability of being BLV-positive at parity ≥5, followed by herd size (OR = 1.8, 95 %CI 1.4–2.2). However, geographic location seems to have no impact on the prevalence of BLV infection in Egypt. Our findings strongly indicate that the intensive surveillance and effective prevention strategies against BLV infection in Egypt should be provided to multiparous cows with ≥5 parities and live in large farm with more than 200 cows.